Impact of preprocedural anticoagulation on the incidence of silent cerebral embolisms after catheter ablation of atrial fibrillation in patients with low thromboembolic risk - Meng Wang; Wei Du; Ya-lan Fei; Hao Yang; Qing-shan Dong; Xian-jin Li; Shi-jie Li; Ru-xing Wang; Bing Han (Frontiers in Cardiovascular Medicine)
ObjectiveThe aim of this study was to investigate the impact of preprocedural anticoagulation on the incidence of silent cerebral embolisms (SCEs) assessed by magnetic resonance imaging (MRI) after catheter ablation of atrial fibrillation (AF) in patients with low thromboembolic risk.Methods and resultsA total of 141 patients with AF who were identified with low thromboembolic risk based on CHA2DS2-VASc score (0 or 1 for males and 1 or 2 for females) were enrolled in this study. According to whether or not oral anticoagulants (OACs) had been administered for more than 3 weeks prior to the procedure, patients were divided into the anticoagulation group (n = 49) and the non-anticoagulation group (n = 92). Pulmonary veins were isolated by utilizing irrigated-tip ablation catheters under the guidance of the Carto system. A cerebral MRI was performed 24 to 48 h after ablation to detect any new-onset SCEs. The incidences of SCEs were compared between the two groups. SCEs were detected in 25 (17.7%) patients. The incidence of SCEs was significantly higher in the non-anticoagulation group compared with the anticoagulation group [22/92 [23.9%] vs. 3/49 [6.1%], P = 0.002]. Multivariate logistic regression analysis showed that the preprocedural application of OACs for more than 3 weeks was the only independent protective factor of SCEs after AF ablation.ConclusionAF ablation carried a substantial risk of SCEs even in patients with low thromboembolic risk. Preprocedural anticoagulation for more than 3 weeks can significantly reduce the incidence of SCEs after ablation in AF patients.